A governance platform for multi-project management in shipyards. (June 2018) - Li, Jinghua; Sun, Miaomiao; Han, Duanfeng; Wu, Xiaoyuan; Yang, Boxin; Mao, Xuezhang; Zhou, Qinghua
Highlights: A governance of projects framework is proposed for better multi-projects management. It enables automatic assignment of system access. It can predict the production plan for a new project with limited information. A prototype system is deployed in a shipbuilding company and proves to be effective and efficient. Abstract: Efficient multiple project management is very important to the project-based industries. Current multi-project studies in shipbuilding focus on designing mathematical models and heuristic algorithms to achieve optimal resource usage. However, due to the rigid requirements on complete information, these models are inapt to support decisions in the early stages (such as the project biding stage) that have been acknowledged more and more critical in the ever fierce market. On the other hand, although pieces of information management software have been developed for project management and production, there are works left to be manually executed, such as production prediction of a new project and control of the temporary system access delegated to business partners, hindering further improvements in work efficiency. To bridge these gaps, this paper innovatively proposes a governance platform architecture based on the theory of Governance of Projects. The framework views organization management as important as project management and adopts a new access control method which helps reduce the manual labor. Moreover, a case-based reasoning algorithm that supports planning prediction with limited information is designed. Finally, a prototype system is developed and tested in a shipyard in China. It proves to be both effective and efficient.